Surface-modified single wall carbon nanohorn as an effective electrocatalyst for platinum-free fuel cell cathodes - Unni, SreeKuttan M.; Ramadas, Sarath; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2015)
Platinum (Pt) and its alloys are routinely used in the cathodes of polymer electrolyte membrane fuel cells (PEMFCs) due to their high electrocatalytic activity in oxygen reduction reactions (ORRs). A variety of alternative materials have been examined as alternatives to Pt, but most of these had low activity and their performance deteriorated even further in use. In the present study an alternate electrocatalyst has been examined, obtained by a simple surface modification of single-walled carbon nanohorns by simultaneous doping with Fe and N at 900 degrees C (FeNCNH-900). This had an ORR activity superior to that of 40 wt% Pt on carbon (Pt/C). Compared to Pt/C, FeNCNH-900 gave a 30 mV improvement in onset potential and a 20 mV gain in half-wave potential in an ORR. Its high activity is the result of the simultaneous modulation achieved by the high surface area and the microporosity of carbon nanohorns, together with the establishment of the desired nitrogen-iron coordinated pyrrolic active centres. The catalyst showed excellent electrochemical stability and, most notably, its ORR activity was still increasing after 1000 cycles. Single-cell fuel cell performance using FeNCNH-900 as cathode catalyst showed a maximum power density of 35 mW cm(-2) under alkaline conditions.

Single cell fabrication towards the realistic evaluation of a CNT-strung ZIF-derived electrocatalyst as a cathode material in alkaline fuel cells and metal-air batteries - Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Sivasankaran, Vijitha P.; Kurungot, Sreekumar (ChemElectroChem, 2017)
The development of an electrocatalyst possessing all the vital requisites of an ideal electrode material, such as high porosity, high conductivity, and high intrinsic electrochemical activity, holds a decisive key in determining the activity of the triplephase boundary in many energy devices like fuel cells and metal-air battery systems. In the present work, highly porous cobalt-based ZIFs are strung along the highly conducive CNT backbone by using a simple one-pot technique at room temperature, which is then utilized to derive a porous, corrosion-resistant, Co nanoparticle-embedded electrocatalyst. Herein, for the first time, the single cell performance of the Co-ZIF-67-derived electrocatalyst has been evaluated by fabricating membrane electrode assemblies of alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) systems. A maximum power density of 296 mW/cm(2) (vs. 317 mW/cm(2) for 40 wt.% Pt/C) and 60 mW/cm(2) (vs. 64 mW/cm(2) for 40 wt.% Pt/C) in the single cells of ZAB and AEMFC systems, respectively, establishes the practical proficiency of the homemade electrocatalyst for cathode applications during realistic system-level validations.
Keywords: Batteries; Carbon nanotubes; Composite materials; fuel cells; metal-organic frameworks

Synthesis of ultrathin PEDOT on carbon nanotubes and shear thinning xanthan Gum-H2SO4 gel electrolyte for supercapacitors - Soni, Roby; Bhange, Siddheshwar N.; Athira, E.; Chetry, Rashmi; Kurungot, Sreekumar (ChemElectroChem, 2019)
Resistance of the electrode material play a vital role for applications in supercapacitors, where lowering the resistance leads to improved performance. Poly(3,4-ethylene dioxythiophene) (PEDOT) possesses high theoretical conductivity; however, the high density of grain boundaries, low accessible surface area, and low rate capability have been pervasive issues affecting the PEDOT-based supercapacitors. To this end, a hydrothermal method is proposed in this work where oxygen functional groups incorporated on the surface of carbon nanotubes (CNTs) are utilized to polymerize 3,4-ethylenedioxythiophene (EDOT). PEDOT forms an ultrathin, well-aligned coating on the surface of CNTs. This arrangement minimizes the number of grain boundaries and increases the electrochemically active surface area. Additionally, a shear-thinning Xanthan gum-H2SO4 gel electrolyte is introduced to overcome the low impregnation of the conventional polyvinyl-based electrolyte due to the hydrophobicity of the CNT-PEDOT composite. A supercapacitor based on this material showed a very low Equivalent Series Resistance (ESR) of 0.31 which leads to a high power density of 74 W cm(-3).
Keywords: gel electrolyte; PEDOT; shear thinning; supercapacitor; xanthan gum